An analysis of the Kuznets curve for the Brazilian municipalities (1991, - Edivo de Almeida Oliveira; João Victor Souza da Silva; Clailton Ataídes de Freitas (Economia & Região, 2017)
This paper aims to empirically analyze the relationship of inverted U of Kuznets (1955) to understand the relationship between economic growth and income distribution in consideration of the effects of migration between urban and rural sectors with different levels of productivity in the Brazilian economy. To do so, a review of the work that applied the Kuznets curve to Brazil is used, in addition to other arguments such as the influence of the accumulation of human capital and the migration of individuals in the dynamics of the Brazilian income distribution for the census data of 1991, 2000 and 2010, at the municipal level. Panel data modeling was used for approximating the Kuznets hypothesis to the econometric tool and the quadratic term of the inverted U ratio between the household income per capita and inequality in the distribution of income in the case of Brazilian municipalities, that is, on average inequality increased until 2000 and declined at the end of the decade in 2010. Another observed result corroborated with the human capital theory in the indicative of that the average increase in the study years of the individuals contributed to the equalization of per capita household income among the Brazilian municipalities. Moreover, it was found, in agreement with Kuznets's (1955) argument, that the relative increase of the urban population did not imply an increase in income inequality in the period analyzed..